2018
DOI: 10.1111/fog.12413
|View full text |Cite
|
Sign up to set email alerts
|

Movement and thermal niche of the first satellite‐tagged Mediterranean spearfish (Tetrapturus belone)

Abstract: The Mediterranean spearfish (Tetrapturus belone) is one of the least‐studied istiophorid billfishes, with little known of its biology, ecology, and behavior. To assess the species’ movement and thermal niche, we analyzed telemetry data from, to our knowledge, the first and only Mediterranean spearfish ever outfitted with a pop‐up satellite archival transmitting tag. Throughout a 29‐day deployment during July and August 2015, the fish travelled in Italian waters of the Tyrrhenian and Ligurian Seas, spending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…However, this requires a tremendous amount of work, hampering general applications to the vast number of invertebrates worldwide. Approaches correlating data on species distributions and ambient temperature (Elith & Leathwick 2009;Arostegui et al 2019) estimate realized thermal niches by accounting for additional ecological dimensions, but depend heavily on high-quality species occurrence data that are rarely available for most invertebrates.…”
mentioning
confidence: 99%
“…However, this requires a tremendous amount of work, hampering general applications to the vast number of invertebrates worldwide. Approaches correlating data on species distributions and ambient temperature (Elith & Leathwick 2009;Arostegui et al 2019) estimate realized thermal niches by accounting for additional ecological dimensions, but depend heavily on high-quality species occurrence data that are rarely available for most invertebrates.…”
mentioning
confidence: 99%
“…Some research has suggested that species facing significant physiological limitations and/or exhibiting frequent surface occupation during daytime may rely on the nighttime migration of scattering layer prey into the epipelagic ( 56 58 ). This interpretation is supported, in some cases, by mesopelagic prey items in the diet of truly epipelagic species, e.g., shortbill spearfish: ( 59 , 60 ). However, recent work suggests that some predators may also target shallow scattering layers in the open ocean during the day ( 61 , 62 ), which may be a more common strategy among surface-oriented, or otherwise physiologically limited, pelagic predators than previously recognized.…”
Section: Discussionmentioning
confidence: 93%
“…This mirrors diel changes in the depth distribution of catchability for other species captured in Pacific longline fisheries (Ward & Myers 2005) that exhibit distinct diel movement patterns (e.g. Abecassis et al 2012, Arostegui et al 2019b, as well as the more restricted descents and increased CPUE of pelagic fishes in regions where they experience vertical habitat compression (Prince & Goodyear 2006, Stramma et al 2012, Carlisle et al 2017, Arostegui et al 2019a. While past telemetry of common mola suggested that they may track vertically migrating prey and feed during the day and night (Sims et al 2009a), more recent animal-borne data from the species revealed they only rarely feed at night (Nakamura et al 2015).…”
Section: Discussionmentioning
confidence: 73%